Odpowiedzi

Najlepsza Odpowiedź!
2010-03-01T17:30:09+01:00
A)6x-24-2=6x-26
b)2x+2-3x+3=-x+5
c)-3y+6+4y+8=y+14
d)5x-5y-5-4x-8=x-5y-13
e)6a+2b-2a+2b=4a+4b
f)x²-x-3x=x²-4x
g)5a²-15a-33a²+165a=-28a²+150a
2010-03-01T17:30:18+01:00
A) 6(x - 4) - 2
6x-24-2


b)2(x + 1) - 3(x - 1)
2x+2-3x+1=-x+3

c)-3(y - 2)+ 4(y + 2)
-3y+6+4y+8=y+14

d)5(x - y - 1)-4(x + 2)
5x-5y-5-4x-8=x-5y-13

e) 2(3a + b) - 2(a - b)
6a+2b-2a-2b=4a

f)x(x - 1)- 3(x * x - x)
x²-x-3x²+3x=2x²+2x

g)5a(a - 3) - 33a(a - 5)
5a²-15a-33a²+165a=28a²+150a